A single-degenerate model for the progenitor of the Type Ia supernova 2002ic - Han, Z; Podsiadlowski, P (Oxford University Press, 2006)
Supernova 2002ic was an atypical Type Ia supernova (SN Ia) with evidence for substantial amounts of hydrogen associated with the system. Contrary to previous claims, we show that its unusual properties can be understood within the framework of one of the most favoured progenitor models, the so-called supersoft channel. This requires that the donor star was initially relatively massive ($\sim 3\Ms$) and that the system experienced a delayed dynamical instability, leading to a large amount of mass loss from the system in the last few $10^4 $yr before the explosion. This can produce the inferred hydrogen-rich circumstellar environment, most likely with a disc-like geometry. However, to apply these models requires a larger accretion efficiency onto the white dwarf than is assumed in present parameterizations. If this is confirmed, it would most likely increase estimates for the frequency of the single-degenerate channel. Based on population synthesis simulations we estimate that not more than 1 in 100 SNe Ia should belong to this subgroup of SNe Ia.